Kecepatan Membaca Tulisan Arab Melayu Kelas 2022 B Dalam Cerita “Orang China Masuk Open” - Delpi Lestari; Lidia Dwi Ariani; Meili Safitri; Hasnah Faizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine and describe the reading speed of Malay Arabic texts for class B class 2022 students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Riau University. The method used in this research is descriptive qualitative and quantitative, with a sample size of 14 students class of 2022 B. The data collection technique used in this research is a test technique by providing a Malay Arabic text to obtain reading speed data with the help of a stopwatch to calculate speed time. Students complete reading Malay Arabic texts. Based on the research results, the reading speed of 2022 B students is 33.56 kpm. This shows that reading speed is still within the low criteria because it does not reach 200 kpm as the average criterion. Thus, the level of reading ability of students in the Indonesian Literature Language Education Study Program, Faculty of Teacher Training and Education, University of Riau class 2022 B is included in the low criteria.